2016
DOI: 10.1016/j.neuroscience.2016.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Neural stem/progenitor cell transplantation for spinal cord injury treatment; A systematic review and meta-analysis

Abstract: Despite the vast improvements of cell therapy in spinal cord injury treatment, no optimum protocol has been developed for application of neural stem/progenitor cells. In this regard, the present meta-analysis showed that the efficacy of the neural stem/progenitor cell (NSPC) transplantation depends mainly on injury model, intervention phase, transplanted cell count, immunosuppressive use, and probably stem cell source. Improved functional recovery post NSPC transplantation was found to be higher in transection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
107
3
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(114 citation statements)
references
References 118 publications
1
107
3
3
Order By: Relevance
“…Recently, numerous studies have confirmed the contribution of NSCs to the recovery of nerve function following spinal cord injury 37 . NSCs are used to repair the damaged nervous system, either by transplantation of cells grown in vitro or by activation of endogenous stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, numerous studies have confirmed the contribution of NSCs to the recovery of nerve function following spinal cord injury 37 . NSCs are used to repair the damaged nervous system, either by transplantation of cells grown in vitro or by activation of endogenous stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…A partir do 25º dia, os animais do grupo CTM apresentavam resultado significativamente maior que os do grupo TP (p<0,05). Os animais dos grupos Adicionalmente, diversos estudos demonstram a capacidade de recuperação neurológica funcional de ratos submetidos à TEA, após utilização de CT, via diferentes mecanismos de ação (Oliveri et al 2014, Zhang & He 2014, Yousefifard et al 2016. Numerosos estudos têm sugerido que é mais provável que as CTM atuem por mecanismos parácrinos transitórios ao invés de sobreviverem por longo prazo e substituírem as células danificadas (Oliveri et al 2014, Han et al 2015.…”
Section: Resultsunclassified
“…, Gabriela F. Siano 2 e Eliane G. Melo secundária é desencadeada por uma série complexa de eventos celulares que induz a morte por apoptose dentro de poucas horas a vários dias após o trauma inicial (Crowe et al 1997, Springer et al 1999, Han et al 2015, Yousefifard et al 2016. Dentre os vários estímulos que promovem ativação dos fatores apoptóticos está a sobrecarga do íon cálcio (Ca 2+ ) no meio intracelular (Springer et al 1999, Oo et al 2015.…”
unclassified
See 1 more Smart Citation
“…There are a few clinical trials of cell therapy for acute or subacute SCI, with 33 or without positive outcome. 34 An acute SCI leads to obvious edema and inflammatory reaction in damaged area, and cell injections may exacerbate injury at this period; so, the spinal cord with an acute injury may not be suitable for direct cell transplantation into injured area.…”
Section: Cell Therapymentioning
confidence: 99%